Keseimbangan Ketersediaan dan Kebutuhan Air Berbasis Tata Guna Lahan di Daerah Aliran Sungai Way Seputih - Sari, Dian Apita; Ramadhan, Fajar Rizky; Berliana, Lia (PT. Pubsains Nur Cendekia, 2025)
Water is an essential resource that supports various life needs, but increasing demand due to population growth and land use changes is often not commensurate with its availability. This study aims to analyze the potential water deficit at the sub-district level by considering the dynamics of land use changes and projections of future water needs in the Way Seputih Watershed area. The analysis was carried out with reference to the Minister of Environment Regulation No. 17 of 2009 through calculations of water carrying capacity based on a comparison between water availability and demand. Land use conversion from agriculture to built-up areas in the central and southern parts of the watershed triggers a decrease in water availability and increases pressure on water resources, indicated by a decreasing trend in carrying capacity, the dominance of deficit conditions, an increasingly critical water use index, and a per capita water availability index that has reached absolute scarcity. These findings underscore the importance of sustainable land use planning and water resource management in maintaining the ecological balance of the Way Seputih Watershed.